Peningkatan Pemahaman Hukum dan Integritas Pemilihan Umum bagi Aktivis Muda Pemilu di Yogyakarta: Improving Young Activists' Understanding of Election Law Enforcement with Integrity - Mukhtar, Mukhtar; Lailam, Tanto; Khasanofa, Auliya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This community service program focuses on increasing the understanding of integrity and election law for young election activists in Yogyakarta. The partners in this service are Rumah Muda Integritas and the Voter Education Network for the People in the Special Region of Yogyakarta. Its background needs to be improved in understanding community partners regarding elections with integrity and enforcement of election law. The service method is carried out through deliberation, planning, realization, and maintenance. The service results showed increased participants' understanding of the implementation of the integrity principle in the 2024 National Election, law election, law enforcement of election, types of electoral offenses, the state institutions that have jurisdiction over dispute resolution, and dispute resolution mechanisms for administrative, ethical, and criminal offenses. Hence, the participants have a solid commitment to oversee the 2024 elections that are democratic, honest, fair, and have integrity.